Efforts to Prevent Gratification in the Ship Crew Recruitment System by the Manning Department at PT Arjuna Samudera Indonesia - Ardelia Ayu Safitri; Trisnowati Rahayu; Teguh Pribadi; Intan Sianturi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The Indonesian shipping industry relies on the recruitment of qualified crew to maintain safety and efficiency, but is vulnerable to bribery that undermines meritocracy. This study aims to evaluate the recruitment system at PT Arjuna Samudera Indonesia, identify potential bribery cases, and analyze the effectiveness of its prevention. Using a descriptive qualitative approach, the population included Crewing Department stakeholders (15 staff, 50 prospective crew), with a purposive sample of 10 key informants. Instruments included semi-structured interviews, observation, and documentation; iterative data analysis via Miles, Huberman, and Saldana (reduction, presentation, verification). The results show a structured process (planning, administration, interviews, checks and balances) without written SOPs, the potential for bribery (money, gifts, nepotism), and the effectiveness of prevention through transparency and multi-layered oversight. The conclusion recommends digital SOPs and ethics training for long-term integrity